2015
DOI: 10.1177/0038038514560262
|View full text |Cite
|
Sign up to set email alerts
|

Creating Vignettes of Early Onset Dementia: An Exercise in Public Sociology

Abstract: Drawing on core principles of public sociology, this article discusses the creation of four theatrical vignettes about living with early onset dementia (symptoms of dementia pre-65). The vignettes were developed through an Image Theatre workshop, involving families living with early onset dementia. They were designed to capture key themes, issues and experiences that emerged from the group's collective experience. While the content of the vignettes speaks to a range of key sociological debates (especially in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…A burgeoning interest in creativity in the context of dementia has also manifested in a growing and diverse body of studies that have used innovative research methods to develop understandings of the subjective experience of living with dementia (e.g. Aadlandsvik, 2008; Bartlett, 2012; Buse & Twigg, 2016; Capstick & Ludwin, 2015; Gjengedal, Lykkeslet, S⊘rb⊘, & Sæther, 2014; Jenkins et al., 2016; Keady, Hydén, Johnson, & Swarbrick, 2017; Kontos, Miller, & Kontos, 2017). Examples of these include co-creational arts-based research methods such as poetry (Aadlandsvik, 2008), drama (Jenkins et al., 2016) and participatory film-making (Capstick & Ludwin, 2015), diary methods (Bartlett, 2012) and methods privileging material and embodied experience (Buse & Twigg, 2014, 2016, 2018; Kontos et al., 2017).…”
Section: Creative Methods Used To Study the Experience Of Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…A burgeoning interest in creativity in the context of dementia has also manifested in a growing and diverse body of studies that have used innovative research methods to develop understandings of the subjective experience of living with dementia (e.g. Aadlandsvik, 2008; Bartlett, 2012; Buse & Twigg, 2016; Capstick & Ludwin, 2015; Gjengedal, Lykkeslet, S⊘rb⊘, & Sæther, 2014; Jenkins et al., 2016; Keady, Hydén, Johnson, & Swarbrick, 2017; Kontos, Miller, & Kontos, 2017). Examples of these include co-creational arts-based research methods such as poetry (Aadlandsvik, 2008), drama (Jenkins et al., 2016) and participatory film-making (Capstick & Ludwin, 2015), diary methods (Bartlett, 2012) and methods privileging material and embodied experience (Buse & Twigg, 2014, 2016, 2018; Kontos et al., 2017).…”
Section: Creative Methods Used To Study the Experience Of Dementiamentioning
confidence: 99%
“…The person-centred paradigm, while enacting a welcome shift in emphasis from the biomedical features of dementia to the person living with the condition, has arguably concretised an individual, rather than relational, focus. We propose that viewing the self as a social, relational process (Jenkins, Keyes, & Strange, 2016) rather than as an atomised, interior phenomenon, may offer a broader perspective on creativity which could be usefully adopted in a critical approach.…”
Section: Researching Arts-based Interventions For People With Dementiamentioning
confidence: 99%
“…Participatory methods were used to involve people with dementia in hands-on processes including filmmaking (Capstick & Ludwin, 2015), writing and acting (Jenkins et al, 2016), diary keeping (Bartlett, 2012), design (Boman et al, 2014;Martin et al, 2013;van Hoof, Sprong, Marston, & Janssen, 2015), and autobiographical narrative production (Benbow & Kingston, 2014). In these studies, innovation was consistently demonstrated in both the hands-on processes and the methods used to explore them.…”
Section: Participatory Methodsmentioning
confidence: 99%
“…The therapeutic potential of engaging in participatory studies was highlighted (Benbow & Kingston, 2014;van Hoof et al, 2015), but participatory methods also included creative processes whose purpose extended beyond the therapeutic. Tangible outputs included the development and testing of assistive technology (Boman et al, 2014;Martin et al, 2013) and the production of filmed theatrical vignettes used for public and academic education (Jenkins et al, 2016). Participatory methods were identified as paying particular attention to issues of power and inclusion and the construction of shared understandings.…”
Section: Participatory Methodsmentioning
confidence: 99%
See 1 more Smart Citation